PaleoProxy Data Base (PPDB): A comprehensive geodatabase to archive and manage paleoproxies data - STRIGARO, DANIELE; MATTAVELLI, MATTEO; DE AMICIS, MATTIA GIOVANNI MARIA; Frigerio, I (Rendiconti Online della Società Geologica Italiana, 2014)
Glaciers are sentinels of climate and environmental change, many marine regions pollen and other biological and geological entities can provide information on past climate variations. The Project of Interest NextData will favour the implementation of measurement networks in remote mountain and marine areas and will develop efficient web portals to access meteoclimatic and atmospheric composition data, past climate information from ice and sediment cores, biodiversity and ecosystem data, measurements of the hydrological cycle, marine reanalyses and climate projections at global and regional scale. In this work a methodology to recover, store, access and disseminate paleoproxies data is presented. Studied proxies are ice and marine cores, sediment cores, tree rings, speleotems (Bradley R. S. 1999). To reach this goal an accurate bibliography research were accomplished to collect data and metadata that were essential to study a suitable methodology to design a correct conceptual scheme between entities to build PPDB structure. The data cover the globe, and while most span the last few millennia, some datasets extend back in time 100 million years. Most of the data are time series of geophysical or biological measurements. The importance to implement a unique database for paleoproxy derived from the necessity of paleoclimate scientists to have a structure that permit the data interoperability to develop new analysis methods based on multi proxy data such as the creation of Italy climatic maps of the last 10-15 ky BP. Furthermore in most cases there is not a geodatabase structure behind data. In PPDB data are not only well stored to permit data interoperability but there are a more efficient and accurate queries to retrieve more detailed informations. Data collected in the spatial geographic database are integrated in an information system through web services as Web Map Service (WMS), Web Feature Service (WFS) to share the geospatial information according to technical specifications proposed by Open Geospatial ...